Pengungkapan Corporate Social Responsibility (CSR) terhadap respon investor dimoderasi oleh kinerja keuangan - Asrini, Asrini; Misrah, Misrah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine the effect of CSR disclosure on investor response, as well as examine financial performance as a reinforcing variable between CSR disclosure and investor response in Islamic banking. This type of research used is quantitative research. The population used in this study are all Islamic banking companies for the period 2018 – 2020 which are listed on the Indonesia Stock Exchange (IDX). The sample selection method in this study used a purposive sampling method. The total sample of this research is 13 companies. The data analysis technique uses the regression model selection test, the classical assumption test and the partial hypothesis test with the SPSS version 22 program. The findings of this study are that CSR disclosure has a positive and significant effect on investor response. Financial performance strengthens the effect of CSR disclosure on investor response.